Audit Layanan Sistem Informasi Bantuan Operasional Sekolah Kabupaten Bintan Menggunakan Cobit 5.0 - Liza Safitri; Sella Matussaqdiah; Hendi Setiawan (LPPM Sekolah Tinggi Teknologi Indonesia Tanjungpinang, 2020)
SIBOS is an Information System for School Operational Assistance which is directly monitored by the Bintan Regency Education Office. The problem with the use of the SIBOS application has not been audited so that the efficiency and capability level of the existing information system is not known. In this study, the capability model is used as a measuring tool for respondents' answers to the questionnaire based on the DSS 5.0 domain DSS (delivery, service and support) framework as well as providing definitions and understanding of the ongoing information technology system processes. Based on the recapitulation of answers from the respondents, the value of the capability level is obtained. The audit took a sample of 40 respondents, and questionnaires were distributed and processed using COBIT 5.0 with the results, SIBOS already has a high level of effectiveness at a value of 3.83 or level 4 (predictable process). The assessment scale based on this research is largely achieved, namely at 71.43%. Level 4 means that the information system is as expected, in good and relevant conditions, mostly achieved, there are no significant weaknesses related to this attribute that may exist in the assessment process.